Metadata for intangible cultural heritage: the case of folk dances - Giannoulakis, Stamatios; Tsapatsoulis, Nicolas; Grammalidis, Nikos (My University, 2018)
It is a fact that states and international organizations are trying to protect and promote intangible cultural heritage. According to UNESCO intangible cultural heritage includes traditions or living expressions inherited from our ancestors and passed on to our descendants. Folk dances are an important part of our intangible cultural heritage, so there is a need to promote and protect them to inherit to the next generations. Beyond digitization of various elements of the dance, proper documentation requires to analyse them (either manually or automatically) and describe all important elements using appropriate metadata. However, although different metadata schemas have been defined in the area of cultural heritage, most are suitable only for tangible heritage, and cannot properly describe elements of intangible cultural heritage. The present study proposes a new metadata schema for describing different elements of folk dance.
Keywords: Intangible cultural heritage; Metadata; Folk dances; Digitization; FRBR